Relationships between isokinetic shoulder evaluation and fitness characteristics of elite French female water-polo players - Olivier, N.; Daussin, F. N. (Journal of Human Kinetics, 2018)
Swimming and throwing are involved in water-polo player performance. These movements have a common biomechanical basis in the use of the internal shoulder rotation and adductor muscles. The aim of the study was to evaluate the relationship between shoulder isokinetic evaluation and throwing velocity as well as swimming performance in female water-polo players. Fifteen high level water-polo players completed two isokinetic shoulder evaluations to determine peak torque of shoulder rotators of the dominant shoulder (concentric and eccentric movements at an angular velocity of 60°·s-1 and concentric movements at an angular velocity of 240°·s-1) and shoulder extensors of both arms (concentric movements at an angular velocity of 60°·s-1 and 240°·s-1). Throwing velocity was measured using a radar gun placed 5 m behind the goal post. Front crawl swimming velocity was determined at 25 m, 100 m and 400 m distances. Concentric peak torque at 60°·s-1 and 240°·s-1 of internal rotators and eccentric peak torque at 60°·s-1 of external rotators were predictors of throwing velocity. The best model to explain the relationship between isokinetic evaluations and throwing velocity was obtained with concentric IR peak torque at 60°·s-1 and eccentric ER peak torque at 60°·s-1 (r2 = 0.52, p = 0.012). Relative total work done and peak torque of shoulder extensors were predictors of 25 m swimming velocity. Shoulder isokinetic evaluations correlate significantly with swimming performance and throwing velocity of female water-polo players. The results may help coaches to develop new strategies such as eccentric dry land training programs to increase both shoulder external rotators strength and throwing velocity.